Orthodontic Metallic Lingual Brackets: The Dark Side of the Moon of Bond Failures? - Maria Francesca Sfondrini (Journal of Functional Biomaterials, 2017)
Lingual orthodontics, among both young and adult patients, increased in popularity during last years. The purposes of the present investigation were to evaluate the shear bond strength (SBS) values and Adhesive Remnant Index (ARI) scores of different lingual brackets compared with a vestibular control bracket. One hundred bovine teeth were extracted and embedded in resin blocks. Four different lingual brackets (Idea, Leone; STB, Ormco; TTR, RMO; 2D, Forestadent) and a vestibular control bracket (Victory, 3M) were bonded to the bovine enamel surfaces and subsequently shear tested to failure utilizing a Universal Testing Machine. SBS values were measured. A microscopic evaluation was performed to obtain ARI scores. Statistical analysis was performed at a statistically significant level of p < 0.05 to determine significant differences in SBS values and ARI Scores. No statistically significant variations in SBS were reported among the different groups. Conversely, significant differences were shown in ARI scores among the various groups. Clinical relevance of the present study is that orthodontists can expect similar resistance to debonding forces from lingual appliances as with vestibular brackets.